Regulation of Hepatitis B Virus Replication by Modulating Endoplasmic Reticulum Stress (ER-Stress) - Md. Golzar Hossain; Keiji Ueda (International Journal of Microbiology)
Hepatitis B virus (HBV), resistant to several antiviral drugs due to viral genomic mutations, has been reported, which aggravates chronic infection and leads to hepatocellular carcinoma. Therefore, host cellular factors/signaling modulation might be an alternative way of treatment for drug-resistant HBV. Here, we investigated the viral protein expression, replication, and virion production using endoplasmic reticulum (ER) stress-modulating chemicals, tunicamycin (an ER-stress inducer), and salubrinal (an ER-stress inhibitor). We found that ER-stress could be induced by HBV replication in transfected HepG2 cells as well as by tunicamycin as demonstrated by dual luciferase assay. HBV intracellular core-associated DNA quantified by qPCR has been significantly increased by tunicamycin in transfected HepG2 cells. Inversely, intracellular core associated and extracellular particle DNA has been significantly decreased in a dose-dependent manner in salubrinal-treated HepG2 cells transfected with HBV-replicating plasmid pHBI. Similar results were found in stably HBV-expressing hepatoblastoma (HB611) cells treated with salubrinal. However, increased or decreased ER-stress by tunicamycin or salubrinal treatment, respectively, has been confirmed by expression analysis of grp78 using Western blot. In addition, Western blot results demonstrated that the expression of HBV core protein and large HBsAg is increased and decreased by tunicamycin and salubrinal, respectively. In conclusion, the sal-mediated inhibition of the HBV replication and virion production might be due to the simultaneous reduction of core and large HBsAg expression and maintaining the ER homeostasis. These results of HBV replication regulation by modulation of ER-stress dynamics would be useful for designing/identifying anti-HBV drugs targeting cellular signaling pathways.